Nocagions: relações entre escrita e notação em John Cage e Hélio Oiticica - Miguel de Avila Duarte (2017)
This research is focused on the writings of the Brazilian visual artist Hélio Oiticica and those of the American composer John Cage. It deals in particular with the relationship between such writings and the multiple forms of notation which, coming from the context of music, becamewidely used in different fields of the arts throughout the 1960s, as well as the place of such artifacts in the contemporary art world and culture at large. To this end we use two different conceptions of interaction between the logics of writing and musical notation score-text and text-score highlighting the connection between them and the practices of orality, writing, visuality and audio recording. The textual preparations that inform and deform Cages writings, notably through non usual strategies of reading, quotations and fragmentation, are examined, as is his peculiar concept of Literature as a space-time hybrid form, defined by his biological analogy with myxomycetes. In Oiticica, we sought the specificity of his writings from the New York period, characterized by the use of writing as a tool and the text as container. It is proposed that such traits are related to the dialogue of the Rio de Janeiro artist with the texts of Cage and other artists in the cagean tradition of the New York avant-garde of that time. Dialogue which is informed, on the one hand, by a interest in music that goes through all phases of Oiticica's workand thought and, on the other, by the artist subversive approach to the geopolitical asymmetry of the art world. Questions about the relevance the artists and the composers work in the contemporary field are asked, stressing the impossibility of confining them in the opposition between modernism and the postmodernism. Both have at the same time been mentioned as validation and questioned in current discussions and both take part of the recent reconfiguration of the ideas of the avant-garde and the experimental in the context of web.